Novel evidence from APEC countries on stock market integration and volatility spillover: A Diebold and Yilmaz approach - Shubham Kakran; Arpit Sidhu; Parminder Kaur Bajaj; Vishal Dagar (Cogent Economics & Finance, 2023)
The interconnection of stock markets offers valuable insights into the broader dynamics of global financial markets. This study uses the Diebold and Yilmaz index model to analyze and measure volatility spillovers and interconnectedness among APEC stock markets. The objective is to identify major transmitters of volatility spillovers and assess the magnitude of different crisis cycles. The results show that the US is the major contributor (69.54%) to volatility spillovers in APEC stock markets, followed by Canada (52.92%) and Mexico (37.09%). These three economies are part of the highly integrated regional bloc, say, North American Free Trade Agreement (NAFTA). New Zealand has the highest net inflow of spillovers, while spillovers account for 32.86% of the error variance across APEC equity markets. Moreover, notable spikes in volatility spillovers have been observed as a result of various events, including the Chinese stock bubble, the Global Financial Crisis (2007-2008), European debt crises, the Chinese stock market crash, the cryptocurrency crash, the COVID-19 pandemic, and the Russia-Ukraine conflict. The study's findings imply that policymakers should enhance economic integration and cooperation within APEC countries to manage volatility spillovers effectively. The research highlights market interactions for a large sample, aiding in identifying investment opportunities and risk management strategies.
Keywords: G15; G18; G1; G14; C32; 330; APEC; crises; Diebold-Yilmaz approach; forecast error variance decomposition; stock market connectedness; volatility spillovers